Manfaat Akuntansi Syariah Dalam Mendorong Pertumbuhan Ekonomi Syariah - Linda Puji Kesuma; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Islamic accounting is an accounting system rooted in Islamic principles, such as fairness, transparency, and social responsibility. This system aims to support ethical economic practices that align with Islamic values, including the prohibition of usury, gharar (uncertainty), and activities that conflict with sharia. This article examines the benefits of Islamic accounting in fostering the growth of the Islamic economy. First, Islamic accounting helps build trust among business stakeholders and the wider community by providing accurate and transparent financial information in line with sharia principles. Second, it promotes more responsible financial management, thereby reducing financial risks that do not comply with sharia. Third, Islamic accounting plays a role in developing Islamic financial instruments, such as sukuk, zakat, and waqf, which serve as sources of productive financing for the Islamic economic sector. Therefore, the effective application of Islamic accounting can stimulate sustainable growth in the Islamic economy, promote financial inclusion, and enhance global economic stability.